Hubungan Aktifitas Fisik, Keputihan, Stress Psikososial Terhadap Ketuban Pecah Dini - Mutia, Febry Mutiariami Dahlan; Sumarni, Aan; Lail, Nurul Husnul (Photon: Jurnal Sain dan Kesehatan, 2022)
PROM is still a public health issue in Indonesia, and it is one of the most common obstetric complications, with high rates of occurrence and fatality. Approximately 6% to 20% of pregnant women will have a miscarriage before 37 weeks of pregnancy, accounting for 5-10% of all births, with 70% occurring at term.Perinatal infection, umbilical cord compression, placental abruption, newborn respiratory distress syndrome, and neonatal sepsis are all possible complications ofPROM. Premature rupture of membranes (PROM) was the most common cause of pathological/complications in pregnant/maternity women at Ciomas Public HealthCenter, and the number of PROM cases increased from the previous year. Aim in this research for analyzing factors related to the incidence of premature rupture of membranesat UPT Public Health Centre, Ciomas, Serang Regency, Banten Province, 2021. This is a quantitative research design that employed a cross-sectional analytic approach. This research used a purposive sampling strategy to select 44 maternity mothers as participants. A questionnaire was employed as the research tool. The information was gathered from primary sources and analyzed using the chi square statistical test. The univariate analysis revealed that PROM was experienced by 45,5 percent of mothers who gave birth, 65,5 percent of mothers who gave birth with high physical activity variables, and 72,7 percent of mothers who gave birth with vaginal discharge. 75 percent of mothers experienced psychosocial stress during pregnancy. The bivariate analysis revealed a significant link between high physicalactivity variables (p = 0,014), vaginal discharge (p = 0,038), and psychosocial stressfactors (p = 0,019) and the risk of early rupture of membranes. It was discovered in this research that many women who gave birth experienced premature rupture of membranes, and that there was alink between high physical activity, vaginal discharge, and psychosocial stress, which could be alleviated by reducing high physical activity, vaginal discharge, andpsychosocial stress